Nutritional supplementation for ewes in late pregnancy: nutritional and metabolic parameters - Siqueira, Marco Túlio Santos (2020)
The objective was to evaluate the effect of supplementation with two levels of concentrate in the diet of sheep in the final third of gestation on how they affect the consumption of dry matter and blood metabolites. The experiments were carried out on 41 sheep with an average weight of 64.2 kg. The animals were housed in pens where the treatments consisted of two levels of concentrate as a supplement, distributed entirely at random with repeated measures over time (according to the prediction of birth of the animals). The diet consisted of corn silage and concentrated in the form of a supplement, offered at 08:00AM and 04:00PM hours, being provided to the animal in order to obtain 10% of leftovers of the total offered of feed. The treatment means were evaluated by the Tukey test at a 5% significance level. For the evaluations of the period, a regression study was used at a significance level of 5%. Among the variables analyzed, dry matter consumption increased throughout the experimental period. Regarding energy metabolites, there was a difference only for the period analyzed with an increase in LDL. Regarding liver enzymes, only aspartate amino transferase was influenced by the evaluation period. Regarding protein metabolites, urea, creatinine and albumin underwent a reduction effect throughout the experimental period. Supplementation of pregnant ewes in the final third of gestation was efficient in improving consumption in the final third of pregnancy, without causing metabolic damage to the animals.